Association of fatty acids and polar compound fractions with acrylamide formation during intermittent frying - Su, Lee Kuek; Ahmad Tarmizi, Azmil Haizam; Abd Razak, Raznim Arni; Jinap, Selamat; Norliza, Saparin; Sanny, Maimunah (Malaysian Palm Oil Board, 2022)
This study aimed to investigate the relationship of fatty acids composition (FAC) and total polar compounds (TPC) on acrylamide formation during intermittent frying of French fries. Four vegetable oils namely palm olein, red palm olein, soybean and sunflower oil were subjected to 80 frying cycles over five consecutive days. The FAC was analysed in the fresh oil (before frying) and 80th frying cycles while TPC was quantified for every 16th frying cycle. The saturated fatty acids (SFA) significantly increased over 80 frying cycles; however, polyunsaturated fatty acids (PUFA) demonstrated a significant reduction. A strong positive correlation (r=0.864, p≤0.05) was observed between acrylamide content and PUFA whereas a weak positive but significant correlation for SFA (r=0.284, p≤0.05) and monounsaturated fatty acids (MUFA) (r=0.358, p≤0.05). Polymerised triacylglycerols (PTAG), oxidised triacylglycerols (OxTAG), and diacylglycerols (DAG) were significantly increased over frying cycles. A weak but significant negative correlation (r=-0.269, p≤0.05) was observed between PTAG in oils and acrylamide in French fries. FAC and PTAG significantly contributed to the formation of acrylamide in French fries. This indicates that lipid oxidation, particularly tertiary oxidation, exhibits a significant contribution to acrylamide development during frying.